Analisis Pembelajaran Statistika Berbasis Literasi menggunakan E-Modul Berbantuan Flipbook - Kusumaningrum, Yulinda; Maulana, Charis (Jurnal Transformatika, 2025)
This research investigates the implementation of literacy-based learning in Statistics through the development of an e-module enhanced with Flipbook technology, aiming to foster student comprehension and active participation. The study employs a Research and Development (R&D) approach, utilizing the 4D model consisting of the phases: Define, Design, Develop, and Disseminate. The main output is a literacy-focused e-module presented in Flipbook format, specifically designed for students in the Informatics Engineering department. Validation from subject matter and media experts confirmed the module’s quality, rating it as “feasible” to “highly feasible.” Feedback from students reflected strong approval, with an overall response score averaging 83.75%, falling into the “very good” category. The use of the module significantly enhanced students’ grasp of statistical concepts, as evident from the improved scores in both pretest and posttest assessments. The recorded average gain score of 0.70, classified as “high,” demonstrates the e-module’s effectiveness in boosting learning outcomes. This integration of technology and literacy within the e-module makes it an appropriate and impactful learning tool to enrich the Statistics learning experience in a more engaging and contextually relevant manner.